2013
DOI: 10.1039/c3sc52027g
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of CO to low-valent phosphorus centres and other related P–C bonding situations. A theoretical case study

Abstract: The multi-faceted bonding of CO in molecular phosphorus compounds is described using calculated P-C bond strengths as a criterion. Full compliance matrices at coupled cluster level of HPCO (1a), singlet oxaphosphirane-3-ylidene HP(h 2 -CO)), the dimer (HPC]O) 2 as well as P^CH, HP]CH 2 and H 2 P-CH 3 were calculated to obtain quantifiable data and enable comparison. The quest for CO coordination and activation was examined for phosphaketenes 1a-f: the P-C compliance constants (inÅ mdyn À1 ) reveal a clear tren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 124 publications
1
27
0
Order By: Relevance
“…For the sake of comparison with N‐donor derivatives previously reported, adducts 1 v – z containing C‐donor ligands have been included in this study. In all cases the P atom has pyramidal geometry (Σ<P=305.6–316.1°; Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…For the sake of comparison with N‐donor derivatives previously reported, adducts 1 v – z containing C‐donor ligands have been included in this study. In all cases the P atom has pyramidal geometry (Σ<P=305.6–316.1°; Table ).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, carbodiimides were successfully transformed into 3‐imino‐azaphosphiridine complexes, despite their thermal lability and exchange tendencies . Maybe the most striking example for this paralleled transition‐metal coordination chemistry was the outcome of a bonding analysis of neutral complexes having CO κC‐bound to a phosphorus centre . Concerning the fixation of CO by non‐metal main group element group 14 centres, related results were reported for a CAAC derivative, yielding a bent ketene, and for silylene H 2 Si forming a Lewis acid base complex with CO ]12] as matrix isolation studies have shown.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…As previously proposed (Scheme ), complex 4 Cr f is also the intermediate resulting from nucleophilic attack of the nitrogen atom of the corresponding model imine ArCHNH ( 3′ ) on the model electrophilic phosphinidene complex 2 Cr . According to a recent report on the reactions of phosphinidene complexes with carbon monoxide,19 the two reagents approach very exergonically20 and in a barrier‐less fashion as no van der Waals complex could be located at the current level of theory. The privileged conformation in 4 Cr f undergoes a kinetically and thermodynamically favoured transformation into the phosphinidene complex 10 Cr f by means of an azaphospha‐Cope [3,3] shift (Scheme ) 21…”
Section: Resultsmentioning
confidence: 99%